Urgensi Konsep dan Teori Uang dalam Islam bagi Siswa SMK IT AL-Izhar Pekanbaru - Saru Reza; Muhammad Syaipudin; Diany Mairiza; Mifta Hasda; Suci Mardiyah (Global Sustainability Research Institute, 2024)
This community service program aims to improve students' understanding of the concept and theory of Islamic finance. This research is motivated by the need to equip the younger generation with in-depth knowledge of financial management following Islamic principles, in order to face economic challenges in the future. The methods used in this program include a participatory and educational approach, with the main activities being interactive learning sessions, financial planning simulations, and group discussions. This program improves students' understanding of the principles of Islamic finance, such as the prohibition of usury, gharar, and maysir. Students not only gain theoretical knowledge but also practical skills in managing finances through Islamic teachings. The positive impacts felt include changes in students' attitudes towards financial management, increased collective awareness of the importance of Islamic financial literacy, and strengthening relationships between students, teachers, and parents. Overall, this program has succeeded in achieving its main objective, which is to equip students with the knowledge and skills to apply Islamic financial principles in their lives, and is expected to contribute to the formation of a financially intelligent young generation committed to Islamic values.